Capital & Labour, Partners?: Two Classes, Two Views - Levant, Victor (Steel Rail Educational, 1977)
There have been many attempts to convince Labor that Capital is a friend. In this book Victor Levant lays bare the ideological basis of the contention that Labor and Capital are partners and in so doing he exposes the mis-leaders of labor who week to take workers along the road paved by Capital. –Publisher's description
OCLC: 4120144
Keywords: Canada; Company unions; Company unions Canada; Company unions North America; Company unions Québec (Province); Company unions United States; North America; Québec; Syndicats d'entreprise Amérique du Nord; Syndicats d'entreprise Canada; Syndicats d'entreprise Québec (Province); Syndicats d'entreprise États-Unis; United States